ANALISIS UNGKAPAN TRADISIONAL DALAM RITUAL VAU DI DESA TAYANDO YAMTEL KECAMATAN TAYANDO TAM (KAJIAN ETNOLINGUISTIK) - Ahmat Renhoat; Susi Hardila Latocinsina; Nanik Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to identify and describe the forms and meanings of symbols embedded in the traditional expressions of the Vau ritual from an ethnolinguistic perspective. A descriptive qualitative method was employed in this study. The research data consist of traditional expressions, which were collected through interviews, observation, and documentation techniques. The results demonstrate that these traditional expressions are structured across several main stages: Wasar (the proposal), Hurak (determining the wedding day), Iyak sit yahau lilan (the exchange of rings), as well as the stages of handing over heirloom dowries (Lela, Mariyam, Gong) and the logistics distribution rite (bawiyar ai). Semiotically, the use of metaphors such as "house flower" (bung funn) represents the purity and dignity of women. Meanwhile, the defensive rhetoric employed during intense dowry negotiations successfully deconstructs material values into a humanist compromise rooted in kinship. The climax of this procession features the chanting of ritual songs (Wiran sowo lar naba wo / Im wo am wo), which functions to dissolve clan differentiation and dismantle social barriers, merging them into a single historical lineage of shared ancestry. This study concludes that the entire formulation of these traditional speeches operates as a robust collective "oral archive" that prioritizes human values.